Evaluation of Fontan failure by classifying the severity of Fontan-associated liver disease: a single-centre cross-sectional study. (28th October 2020) - Schleiger, Anastasia; Kramer, Peter; Salzmann, Madeleine; Danne, Friederike; Schubert, Stephan; Bassir, Christian; Müller, Tobias; Tacke, Frank; Müller, Hans-Peter; Berger, Felix; Photiadis, Joachim; Ovroutski, Stanislav
Abstract: OBJECTIVES: Fontan-associated liver disease (FALD) is a hallmark of the failing Fontan circulation, but no general classification of FALD severity exists. In this study, we propose a scoring system to grade the severity of FALD and analyse its applicability for evaluation of Fontan failure. METHODS: From 2017 to 2019, a total of 129 successive Fontan patients received a comprehensive hepatic assessment. The FALD score was based on results from laboratory testing, hepatic ultrasound and transient elastography by assigning scoring points for each abnormality detected. FALD severity was graded mild, moderate and severe. Haemodynamic assessment was performed using echocardiography, cardiopulmonary exercise testing and catheterization. RESULTS: FALD was graded absent/ mild, moderate and severe in 53, 26 and 50 patients, respectively. Cardiopulmonary capacity was significantly impaired in patients with severe FALD compared to patients with absent/mild FALD ( P  =   0.001). The FALD score significantly correlated with pulmonary artery pressure ( P  =   0.001), end-diastolic ventricular pressure ( P  <   0.001), hepatic venous pressure ( P  =   0.004) and wedged hepatic venous pressure ( P  =   0.009). Fontan failure was present in 21 patients. FALD was graded moderate in 2 and severe in 19 of these patients. The FALD score accurately discriminated patients with and without Fontan failure (sensitivity 90.5%, specificity 71.3%). CONCLUSIONS: The FALD score significantly correlates with impaired Fontan haemodynamics. A cut-off value ≥6.0 has a high diagnostic accuracy in detecting Fontan failure. Clinical trial registry: DRKS (GCTR, German clinical trial registry) Clinical trial registration number: DRKS00015039 Abstract : Over the past decades, survival of Fontan-palliated patients significantly improved with the majority of patients now reaching adulthood [1, 2].